Multicell cooperation for LTE-Advanced Heterogeneous Network scenarios - Soret, Beatriz; Wang, Hua; Pedersen, Klaus I.; Rosa, Claudio (IEEE, 2013)
In this article we present two promising practical use cases for simple multicell cooperation for LTE-Advanced heterogeneous network scenarios with macro and small cells. For co-channel deployment cases, we recommend the use of enhanced interference coordination, or eICIC, to mitigate cross-tier interference and ensure sufficient offload of users from macro to small cells. It is shown how the eICIC benefit is maximized by using a distributed inter-base station control framework for dynamic adjustment of essential parameters. Second, for scenarios where macro and small cells are deployed at different carriers an efficient use of the fragmented spectrum can be achieved by using collaborative inter-site carrier aggregation. In addition to distributed coordination/collaboration between base station nodes, the importance of explicit terminal assistance is highlighted. Comprehensive system-level simulation results illustrate the performance benefits of the presented techniques.
https://openpolicyfinder.jisc.ac.uk/id/publication/37970
Keywords: LTE (Telecomunicaciones); Sistemas de comunicación inalámbricos; HetNets; Interference management; LTE advanced; Multicell cooperation